EFFECTS OF PAMIDRONATE ADMINISTRATION ON TOOTH ERUPTION AND MANDIBULAR GROWTH IN NEW BORN RATS - İbrahim Tuncer; Çağrı Delilbaşı; Ediz Deniz; Merva Soluk Tekkesin; Vakur Olgaç; Kemal Şençift (Istanbul University, 2017)
Purpose: Bisphosphonates are commonly used drugs in pediatric patients in the treatment of osteoporotic diseases and various types of cancers. The purpose of this study was to evaluate the effects of pamidronate administration on mandibular growth and tooth eruption in new born rats. Materials and Methods: Forty Sprague Dawley rats were included in the study and divided into four groups as; 14th day pamidronate group, 30th day pamidronate group, 14th day control group and 30th day control group. Pamidronate groups were daily injected with 1.25 μg/g pamidronate disodium subcutaneously whereas control groups were injected with sterile saline. Eruption levels of lower incisor and molar teeth were assessed macroscopically. Mandibular growth was assessed by measuring reference points in cone beam tomography. Histological and histomorphometric examinations were performed under light microscope to evaluate tooth morphology and number of osteoclasts. Results: Retardation in mandibular growth, decrease in number of osteoclasts, delay in tooth eruption, degeneration in both tooth morphology and structure were observed in the pamidronate groups compared to control groups. Conclusion: Pamidronate administration during growth and development stage may adversely affect tooth eruption and mandibular growth in new born rats.